Inhibition of ANO1/TMEM16A Chloride Channel by Idebenone and Its Cytotoxicity to Cancer Cell Lines - Seo, Yohan; Park, Jinhong; Kim, Minseo; Lee, Ho K.; Kim, Jin-Hee; Jeong, Jin-Hyun; Namkung, Wan (PloS one, 2015)
The expression levels of anoctamin 1 (ANO1, TMEM16A), a calcium-activated chloride channel (CaCC), are significantly increased in several tumors, and inhibition of ANO1 is known to reduce cell proliferation and migration. Here, we performed cell-based screening of a collection of natural products and drug-like compounds to identify inhibitors of ANO1. As a result of the screening, idebenone, miconazole and plumbagin were identified as novel ANO1 inhibitors. Electrophysiological studies showed that idebenone, a synthetic analog of coenzyme Q10, completely blocked ANO1 activity in FRT cells expressing ANO1 without any effect on intracellular calcium signaling and CFTR, a cAMP-regulated chloride channel. The CaCC activities in PC-3 and CFPAC-1 cells expressing abundant endogenous ANO1 were strongly blocked by idebenone. Idebenone inhibited cell proliferation and induced apoptosis in PC-3 and CFPAC-1 cells, but not in A549 cells, which do not express ANO1. These data suggest that idebenone, a novel ANO1 inhibitor, has potential for use in cancer therapy.